2016
DOI: 10.1007/s00167-016-3995-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinematically aligned TKA can align knee joint line to horizontal

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 28 publications
11
69
1
Order By: Relevance
“…The pooled mean difference in TCRTMA was 2.25°(95% CI: 1.56-2.95°P < .0001; I 2 = 0%, Fig. 6), indicating that the TCRTMA was significantly more varus with the KA technique [18] 2016 RCS 65 65 N/S KA: N/S MA: N/S 6 JLOA Young et al [19] 2016 …”
Section: Overall Radiographic Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…The pooled mean difference in TCRTMA was 2.25°(95% CI: 1.56-2.95°P < .0001; I 2 = 0%, Fig. 6), indicating that the TCRTMA was significantly more varus with the KA technique [18] 2016 RCS 65 65 N/S KA: N/S MA: N/S 6 JLOA Young et al [19] 2016 …”
Section: Overall Radiographic Outcomementioning
confidence: 99%
“…This eventually resulted in 6 studies that were included in the meta-analysis. [14][15][16][17][18][19] 3.2. Study characteristics, patient populations, and quality assessment of the included studies The 6 studies we examined included 371 patients who underwent primary TKA through the KA technique and 372 patients who underwent primary TKA through the MA technique.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…KA in the coronal and sagittal plane was achieved using a cartilage probing technique previously described. 1 Long-leg standing radiographs were taken for the control and study groups. To control the rotation and position of lower extremities for the AP radiograph, foot orientation angle and distance between both feet were positioned on a reference foot template.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15] The general principle of KATKA is the restoration of the prearthritic knee articular surface to account for individual anatomical variation. A recent study reported the restoration of a native knee joint line which was parallel to the ground after KATKA 1,16 and additional studies show that KATKA actually restores the native forces in the medial and lateral joints. 17,18 Theoretically, restoration of the prearthritic knee articular surface would restore the relationship between the native knee and adjacent joints.…”
mentioning
confidence: 97%
See 1 more Smart Citation